Relationship between anxiety and spiritual well-being of the elderly with hypertension during the COVID-19 pandemic - Iswatun; Yusuf, Ah; Efendi, Ferry; Susanto, Joko; Kumala Dewi, Winda; Hidaayah, Nur (Journal of the Pakistan Medical Association, 2023)
Objective: To study the relationship between anxiety and the spiritual wellbeing of hypertensive elderly patients during the corona virus disease-2019 pandemic. Method: The cross-sectional, correlational, analytical study was conducted from March to May 2022 in Lamongan Regency, East Java, Indonesia, after approval from the Faculty of Nursing, Universitas Airlangga, Surabaya, Indonesia, and comprised elderly hypertensive subjects aged >45 years who had good cognitive skills. Data was collected using the Geriatric Anxiety Scale and the Spiritual Wellbeing Scale. Anxiety was the independent variable, while spiritual wellbeing was the dependent variable. Data was analysed using univariate and bivariate analyses. Results: Of the 200 subjects, 107(53.5%) were females and 93(46.5%) were males. Overall, 97(48.5%) were aged 45-49 years, 81(40.5%) had completed primary school, 96(48%) were farmers, 121(60.5%) had moderate anxiety and 80(40%) had moderate spiritual wellbeing. There was a significant relationship between anxiety and spiritual wellbeing (p<0.05). Age, education and occupation of the subjects had significant association with both anxiety and spiritual wellbeing (p<0.05). Conclusion: The coronavirus disease-2019 led to decreased anxiety and increased spiritual wellbeing among the hypertensive elderly. Keywords: COVID-19, Anxiety, Hypertension, Cognition, Prognosis.